2017
DOI: 10.1177/2158244017715076
|View full text |Cite
|
Sign up to set email alerts
|

Social Intelligence and the Explanation of Workplace Abuse

Abstract: Bullying in the workplace by management-level supervisors and executives has been well documented in the literature; however, bullying of employees by their associates is often less noticeable, even stealth, and has been understudied. This article presents a theoretical model that draws from the literature of clinical psychology and recent research in neuroscience to identify and describe the four different roles played in employee workplace colleague abuse. These roles include (1) the leader of the abuse, (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The study also showed that vertical bullying has several negative consequences for the bullied as well as for the organization itself. The types of consequences detailed in this study and presented previously in the concept consequences of vertical bullying, which is composed by eight factors, verify the results from previous studies, including Einarsen (2005), Hoel et al (2010), Salin (2003), Popp (2017) and Salin and Notelaers (2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The study also showed that vertical bullying has several negative consequences for the bullied as well as for the organization itself. The types of consequences detailed in this study and presented previously in the concept consequences of vertical bullying, which is composed by eight factors, verify the results from previous studies, including Einarsen (2005), Hoel et al (2010), Salin (2003), Popp (2017) and Salin and Notelaers (2017).…”
Section: Discussionsupporting
confidence: 88%
“…The targets of workplace bullying experience both psychological and physical issues, including anxiety and distress caused by increased levels of cortisol. Often, they interpret this reaction as a sign of personal weakness (Hoel and Salin 2003;Popp 2017). This is line with the demand-control model (Karasek 1979(Karasek , 1989Karasek and Theorell 1990) that states employees experience high levels of stress, which can also affect their physical health when exposed to high-demand and low-control situations.…”
Section: Workplace Bullyingmentioning
confidence: 79%
See 1 more Smart Citation
“…Further research by Jerome Popp (2017) showed that someone with a high social intelligence is very easy to feel empathic, more easily understand what other people think and their intentions, as well as better understand and interpret the comments of people who interact with it. Likewise, a study conducted by Kriemeen (2017) concluded there is a correlation between social intelligence and social creative behavior with positive and significant correlation.…”
Section: Hypothesis Testing Product Moment Correlation (Simplified)mentioning
confidence: 99%
“…Social intelligence includes the ability of individuals in a group to work in collaboration, communicate with other people, understand others more easily and value their feelings (Ünver & Semiz, 2016;Popp, 2017), enabling individuals to live healthily with other individuals and solve problems of social life at the same time, and helps them to perform various social tasks (Saxena & Jain, 2013).…”
Section: Introductionmentioning
confidence: 99%